Subacute effects of inhaled Jet Fuel-A (Jet A) on airway and immune function in female rats. (April 2013) - Sweeney, Lisa M.; Prues, Susan L.; Reboulet, James E.
Abstract Two studies were conducted to assess the potential airway and immune effects following subacute (14 d) exposure of female rats to 500, 1000 or 2000 mg/m3 of Jet-A for 4 h/d. The first study used Sprague-Dawley rats; the second study included both Fischer 344 (F344) and Sprague-Dawley rats. In the first study, exposure to 2000 mg/m3 jet fuel may have caused significant upper airway inflammation on day 7 post-exposure, as indicated by elevated protein and lactate dehydrogenase in nasal lavage fluid, but any inflammation resolved by day 14 post-exposure. No significant impact on immune cell populations in the spleens was observed. The histological examination showed no evidence of infectious or toxic effect. In the second study, body weights of the F344 rats in the 2000 mg/m3 group were depressed, as compared to the controls, at the end of the exposure. Some lung lavage fluid markers were increased at 24 h after the final exposure, however, no test article-induced histological changes were observed in the lungs, nasal cavities, or any other tissue of any of the jet fuel exposed animals. Overall, these studies demonstrated limited evidence of effects of 14 d of exposure to Jet A on the airways, immune system, or any other organ or system of female Sprague-Dawley and F344 rats, with no remarkable differences between strains. The lack of identified significant airway or immune effects was in contrast to previous examinations of jet fuel for pulmonary toxicity in mice and rats and for immunotoxicity in mice.